1999
DOI: 10.1128/aac.43.3.543
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Function Studies of Ser-289 in the Class C β-Lactamase from Enterobacter cloacae P99

Abstract: Site-directed mutagenesis of Ser-289 of the class C β-lactamase from Enterobacter cloacae P99 was performed to investigate the role of this residue in β-lactam hydrolysis. This amino acid lies near the active site of the enzyme, where it can interact with the C-3 substituent of cephalosporins. Kinetic analysis of six mutant β-lactamases with five cephalosporins showed that Ser-289 can be substituted by amino acids with nonpolar or polar uncharged side chains without altering the catalytic efficiency of the enz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 57 publications
0
12
0
Order By: Relevance
“…It has been previously described that substitutions of catalytic residues Ser64, Lys67, Tyr150, Asn152 and Lys315 decreased the activity of the enzyme by 10 3 - to 10 5 -fold compared to AmpC wild-type (Beadle & Shoichet, 2002); nevertheless, residues Gln191 and Pro209, in which mutations were identified in Caz/20-2 mutant (), have not been described as being among those involved in the catalytic function of AmpC β-lactamases. It must not be overlooked that some mutations modifying the length and charge of the side chain of a certain residue can create electrostatic interactions that slow or decrease the catalytic activity of the AmpC β-lactamase, such as previously described for Ser289 residue (Trépanier et al ., 1999), which is not essential in the binding or hydrolytic mechanism of class C β-lactamase from Enterobacter cloacae P99. However, when (Trépanier et al ., 1999) substituted it by Lys or Arg (polar and positively charged residues), it resulted in decreased catalytic activity (Trépanier et al ., 1999).…”
Section: Resultsmentioning
confidence: 98%
“…It has been previously described that substitutions of catalytic residues Ser64, Lys67, Tyr150, Asn152 and Lys315 decreased the activity of the enzyme by 10 3 - to 10 5 -fold compared to AmpC wild-type (Beadle & Shoichet, 2002); nevertheless, residues Gln191 and Pro209, in which mutations were identified in Caz/20-2 mutant (), have not been described as being among those involved in the catalytic function of AmpC β-lactamases. It must not be overlooked that some mutations modifying the length and charge of the side chain of a certain residue can create electrostatic interactions that slow or decrease the catalytic activity of the AmpC β-lactamase, such as previously described for Ser289 residue (Trépanier et al ., 1999), which is not essential in the binding or hydrolytic mechanism of class C β-lactamase from Enterobacter cloacae P99. However, when (Trépanier et al ., 1999) substituted it by Lys or Arg (polar and positively charged residues), it resulted in decreased catalytic activity (Trépanier et al ., 1999).…”
Section: Resultsmentioning
confidence: 98%
“…So far, the research on the structural determinants of class C ES β‐lactamases has been focused on the Ω‐loop of the R1 site because the only class C ES β‐lactamase whose structure is available is GC1 β‐lactamase with an insertion mutation in the Ω‐loop. However, various mutations localized in the R2 site, especially in the R2‐loop, have been reported to change the substrate spectrum of P99 β‐lactamase (Siemers et al ., 1996; Morosini et al ., 1998; Trepanier et al ., 1999; Barnaud et al ., 2001; Vakulenko et al ., 2002), which clearly point to the importance of the R2 site in the hydrolysis of β‐lactam antibiotics. Taking the extent of structural alterations into account therefore the R2 site rather than the R1 site appears to contribute predominantly to the ES activity of CMY‐10.…”
Section: Resultsmentioning
confidence: 99%
“…Crude preparation of β‐lactamases from the M1 and NCTC‐235T strains (grown with or without 5, 10 and 20 mM salicylate) were obtained from sonicated cells and β‐lactamase activity was measured using UV spectrophotometry as previously described [1]. Phenylmethanesulfonyl fluoride, PMSF (Sigma, Madrid, Spain), was used to inhibit the effect of serine proteases that could inactivate AmpC β‐lactamases as previously described [5]. Thus, all β‐lactamase extracts were obtained from bacterial cell suspensions treated with 1 mM PMSF before sonification, previously we had confirmed that PMSF did not modify hydrolytic activity of β‐lactamase crude extracts from the M1 and NCTC‐235T strains.…”
Section: Methodsmentioning
confidence: 99%